ANALISIS DETERMINAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KABUPATEN BANTUL - Faza Fakhriyan Wildan; Umi Sulistiyanti (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2017)
There are 94,632 individual taxpayer listed in Bantul Pratama Tax Office, but only about 45,223 individual taxpayer that pay and report tax.The low individual tax compliance, which is a classic problem of taxation in Indonesia, can be caused by several reasons. The aim of this study is to analyze the influence of tax penalties,educational level, Use of E-filing and tax socialization on the tax compliance of individual taxpayer listed in Bantul Pratama Tax Office. This study is a quantitative research. The samples used in this study were 100 respondents calculated by the Slovin formula and using simple random sampling method. The data were collected using questionnaire method and analyzed using multiple regressions by means of SmartPLS 3.0. The results of this study show that tax penalties have positive effects significantly, while level of education, use of efiling and tax socialization have no effect on tax compliance of individual taxpayer listed in Bantul Pratama Tax Office.